Clinical Manifestation, Surveillance, and Complication in Tuberous Sclerosis Complex in Dr. Moewardi Hospital - Hamidi, Baarid Luqman; Mirawati, Diah Kurnia; Danuaji, Rivan; Subandi, Subandi; Budianto, Pepi; Hambarsari, Yetty; Prabaningtyas, Hanindya (Indonesian Journal of Medicine, 2020)
Background: Tuberous Sclerosis Complex (Bourneville’s disease) is genetic disorder with autosomal pattern of heritence that affecting differentiation sellular in many organ such as brain, lungs, cardiac with varible severity. Birth incidence is estimated to be 1:6000. The purpose of this study was to reported a case of patients with Bourneville’s disease (tuberous sclerosis complex) in Moewardi Hospital. Also reported surveillance and complication in this patient.Case Presentation: A male, 18 yearsold, with seizures, onset from infancy, tonic secondary generalized seizure pattern simultaneously throughout the body. Neurologic status examination found right hemiparese and mental retardation, Encountered in patients with skin disorders such as butterfly appearance with facial angiofibroma, forehead fibrous plaque dan shargreen patch. Abnormalities also appeared in the oral mucosa as multiple papules. When psychological tests patient had difficulty following instructions. Psychiatric examination showed moderate lower intelegence. EEG results slow waves at left parietal, there is severe electrofisiologic abnormality considered structural lesion in left parietal. CT showed multiple calcified nodules in subependymal right and left lateral ventricle. MRI showed  atrophy and left sclerotic hippocampus with glosis in sub cortex occipito left parietal. To overcome the seizure patients given Carbamazepine. There was increasing of transaminase enzim, liver suspect liver angiomyolipoma.Conclusion: Based on clinical criteria for definite tuberous sclerosis complex patients met the criteria. The patients responded positively to carbamazepine that reduced seizure frequency. But somehow, patient's prognosis is worst. Presence of intellectual impairment and neuropsychiatric problems is a potential poor epilepsy control, and liver disfunction so that the necessary comprehensive management and surveillance involves other disciplines.Keywords:Tuberous sclerosis complex, congenital disorder, epilepsy, mental retardationCorrespondence: Baarid Luqman Hamidi.Department of Neurology, Dr. Moewardi Hospital/Faculty of Medicine, Universitas Sebelas Maret. Email: baarid@staff.uns.ac.idIndonesian Journal of Medicine (2020), 05(01): 47-51https://doi.org/10.26911/theijmed.2020.05.01.07